INFLUENCE OF EXOGENOUS APPLICATION OF ABSCISIC ACID IN GAS EXCHANGES OF Hymenaea courbaril L. (FABACEAE) SEEDLINGS SUBJECTED TO WATER DEFICIT - Freitas, Vanessa de Mauro Barbosa; Scalon, Silvana de Paula Quintão; Dresch, Daiane Mugnol; Bastos, Sara da Silva; Souza, Ana Paula Rissato de (Floresta, 2018)
This study was carried out in the greenhouse of the Federal University of Grande Dourados (UFGD), in the municipality of Dourados, state of Mato Grosso do Sul, Brazil, from April to May of 2015. The aim of this study was to assess the effect of different concentrations of abscisic acid (ABA) on the responses under water stress and recovery of Hymenaea courbaril L. seedlings after reirrigation. The following six treatments were assessed: 1) Irrigation with no ABA; 2) Irrigation + 10 µM ABA; 3) Irrigation + 100 µM ABA; 4) No irrigation nor ABA; 5) No irrigation + 10 µM ABA; and 6) No irrigation + 100 µM ABA. No irrigation treatment consisted on water suspension until the photosynthetic rate was close to zero. The plants were then irrigated daily to maintain 70% of the water holding capacity of the soil for a 12-days recovery period. ABA doses applied exogenously during the no irrigation period neither prevented the reduction of photosynthetic activity nor optimized the recovery of gas exchanges and carboxylation efficiency of Rubisco after water and seedling quality restoration. The concentration of 100 µM ABA promoted the degradation of chlorophylls independently of irrigation, which shows that high concentrations of ABA may cause a residual effect on this species. The seedlings exhibited normal metabolic recovery after about 12 days of reirrigation of the soil due to the characteristics of the species and not the tested treatments.